Model Pembelajaran Blended Learning: Implementasi pada Peningkatan Kompetensi Pedagogik dan Kompetensi Profesional Dosen - Wohon, Frimsi; Sumual, Ferry Johnny Nicolaas; Rakim, Ristan (TELEIOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
Abstract: This article discusses the implementation of blended learning model to improve pedagogical competence and professional competence of lecturers. The formulation of this research problem is how the implementation of blended learning models can improve the pedagogical competence and professional competence of lecturers? The researcher used a qualitative research method with a descriptive approach that involved the participation of lecturers as research subjects. Data were collected through surveys, observations, interviews, and document analysis.  The main objective of this research is to investigate the impact of using blended learning model on improving the pedagogical competence and professionalism of lecturers. The application of the blended learning model had a positive impact on the pedagogical competence and professional competence of lecturers. On the improvement of lecturers pedagogical competence, Blended Learning helps lecturers improve their understanding of the learning process, mastery of learning technology and how to prepare effective learning by improving the ability to design interesting and relevant teaching materials, as well as the ability to deliver materials more interactively. The improvement of lecturers professional competence can also be reflected in the promotion of lecturers academic positions, lecturers publications in accredited national and even reputable international journals and extensive community service.Abstrak: Artikel ini membahas implementasi model pembelajaran blended learning untuk meningkatkan kompetensi pedagogik dan kompetensi profesional dosen. Rumusan masalah penelitian ini adalah bagaimana implementasi model pembelajaran blended learning dapat meningkatkan kompetensi pedagogik dan kompetensi profesional dosen? Peneliti menggunakan metode penelitian kualitatif dengan pendekatan deskriptif yang melibatkan partisipasi dosen sebagai subjek penelitian. Data dikumpulkan melalui survei, observasi, wawancara, dan analisis dokumen.  Tujuan utama penelitian ini adalah untuk menginvestigasi dampak penggunaan model pembelajaran blended learning terhadap peningkatan kompetensi pedagogik dan profesionalisme dosen. Dalam penerapan model pembelajaran Blended Learning memberi dampak positif pada kompetensi pedagogik dan kompetensi profesional dosen. Pada peningkatan kompetensi pedagogik dosen, Blended Learning membantu dosen meningkatkan pemahaman mereka tentang proses pembelajaran, penguasaan teknologi pembelajaran dan bagaimana mempersiapkan pembelajaran yang efektif dengan peningkatan kemampuan merancang bahan ajar yang menarik dan relevan, serta kemampuan menyampaikan materi dengan lebih interaktif. Peningkatan kompetensi profesional dosen dapat tergambar juga pada kenaikan pangkat jabatan akademik dosen, publikasi dosen pada jurnal nasional terakreditas bahkan internasional bereputasi serta pengabdian masyarakat secara luas.